2007
DOI: 10.1373/clinchem.2007.089144
|View full text |Cite
|
Sign up to set email alerts
|

Novel Serum Biomarker Candidates for Liver Fibrosis in Hepatitis C Patients

Abstract: Background: Liver biopsy is currently the gold standard for assessing liver fibrosis, and no reliable noninvasive diagnostic approach is available. Therefore a suitable serologic biomarker of liver fibrosis is urgently needed. Methods: We used a proteomics method based on 2-dimensional gel electrophoresis to identify potential fibrosis biomarkers. Serum samples from patients with varying degrees of hepatic scarring induced by infection with the hepatitis C virus (HCV) were analyzed and compared with serum from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
123
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(138 citation statements)
references
References 39 publications
12
123
2
1
Order By: Relevance
“…Among the genes participating in inflammation, A2M was always used as a biological indicator to assess hepatic fibrosis and cirrhosis, and was found to be up-regulated at 3 weeks in this study. Gangadharan et al (2007) pointed out that the expression of A2M was strengthened with the development of hepatic fibrosis, which was consistent with the current study result. Wald et al (2004) found that up-regulation of CXCL12 in liver during chronic HCV and HBV infection may support the establishment of a chronic inflammatory state and a progressive fibrotic process, thus the down-regulation of CXCL12 at 6 and 9 weeks lead to inflammation response inhibition, as shown in Figure 5A and indicated an accordingly result.…”
Section: Discussionsupporting
confidence: 92%
“…Among the genes participating in inflammation, A2M was always used as a biological indicator to assess hepatic fibrosis and cirrhosis, and was found to be up-regulated at 3 weeks in this study. Gangadharan et al (2007) pointed out that the expression of A2M was strengthened with the development of hepatic fibrosis, which was consistent with the current study result. Wald et al (2004) found that up-regulation of CXCL12 in liver during chronic HCV and HBV infection may support the establishment of a chronic inflammatory state and a progressive fibrotic process, thus the down-regulation of CXCL12 at 6 and 9 weeks lead to inflammation response inhibition, as shown in Figure 5A and indicated an accordingly result.…”
Section: Discussionsupporting
confidence: 92%
“…Although the exact mechanism by which ZAG actively participates in tumor proliferation is not known, a large body of data exists in favor of the expression of ZAG with respect to the stages of tumor (39)(40)(41)(42). ZAG is designated as a potential biomarker of different types of carcinomas (6,7,27,35,38,(43)(44)(45)(46).…”
Section: Zag As a Biomarkermentioning
confidence: 99%
“…This protein was also differentially expressed between HIV-1-resistant women and control groups and downregulated by threefold in cervical mucosa of HIV-1-resistant women (Burgener et al, 2008). Gangadharan et al (2007) showed that both C3 and TTR were downregulated in the sera of hepatitis C patients with liver fibrosis.…”
Section: Discussionmentioning
confidence: 93%